Pengaruh Kebijakan Hutang, Profitabilitas, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderating Pada Perusahaan Manufaktur Sektor Industri Barang Dan Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021 - Maimanah (Jurnal Sosial Ekonomi Bisnis, 2021)
The purpose of This study to determine the effect of debt policy, profitability, and firm size on firm value dividends as moderating variables in manufacturing companies in the consumer goods and industrial sector listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. The population of this study were 54 manufacturing companies in the consumer goods and industrial sector listed on the Indonesia Stock Exchange (IDX). The sampling method used is purposive sampling method, in order to obtain 11 sample companies with 5 years of observation so that the total sample is 55 data for 5 years. The research data were obtained from sample companies which were downloaded from the Indonesia Stock Exchange website. The data analysis method used in this research is descriptive analysis, classical assumption test, multiple regression test, hypothesis testing, Modereted Regression Analys (MRA) test and determinant coefficient test.Based on the results of data processing through IBM SPSS Statistic Software that has been analyzed, so that the results of this study are obtained, namely debt policy has no effect on firm value. Profitability has a positive and significant effect on firm value. Firm size has no effect on firm value. And the results of data processing Moderated Regression Analys (MRA), concluded that dividend policy is not able to moderate the effect of debt policy, profitability, and firm size on firm value.